1983
DOI: 10.2134/agronj1983.00021962007500030011x
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Responses to Irrigation Treatment and Environment1

Abstract: Water management is critical for maximum production of alfalfa (Medicago sativa L.) with under irrigation resulting in loss of production and over irrigation resulting in a loss of stand. The purpose of this study was to determine the optimum irrigation rates under high evaporative demand. Growth of alfalfa was evaluated on replicated plots (6 × 6 m) established on a fine textured soil (Typic Torrifluvent, clayey over loamy, montmorillonitic, calcareous hyperthermic family) and differentially irrigated from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 2 publications
3
15
0
Order By: Relevance
“…2A). This was a typical production pattern when compared to reports in similar climatic conditions (Donovan and Meek, 1983). Actual yields Year were low in the spring, improved as day length increased, and dropped in the fall.…”
Section: First Experimentssupporting
confidence: 72%
“…2A). This was a typical production pattern when compared to reports in similar climatic conditions (Donovan and Meek, 1983). Actual yields Year were low in the spring, improved as day length increased, and dropped in the fall.…”
Section: First Experimentssupporting
confidence: 72%
“…In trials on seven crop species, Jensen (1973) showed that alfal fa had the highest water consumption per year and the lowest water-use efficiency. Christian (1977) Alfalfa yields are a linear function of plant-water use (Bauder et al, 1978;Sammis, 1981;Donovan and Meek, 1983).…”
Section: Water Stress Effects On Alfalfa Growthmentioning
confidence: 99%
“…But the response of CP concentration in alfalfa to water stress seems to be in fluenced by additional environmental factors as well. For instance, Donovan and Meek (1983) found that CP concentration of forage was higher under low-moisture treatments in cool months but not in warm months. Nuttall (1975) Surveys of the literature (Wilson, 1982(Wilson, , 1983a, cover ing grasses and legumes in the tropical and temperate regions of the world, indicate that low soil moisture generally has a favorable effect on forage quality.…”
Section: Root Growthmentioning
confidence: 99%
See 2 more Smart Citations